Cu5FeS4 Nanoparticles With Tunable Plasmon Resonances for Efficient Photothermal Therapy of Cancers - Yuan, Lei; Hu, Weiwei; Zhang, Hui; Chen, Long; Wang, Jianyu; Wang, Qiang (Frontiers in Bioengineering and Biotechnology, 2020)
Localized surface plasmon resonances (LSPRs) in heavily doped copper chalcogenides are unique because LSPR energy can be adjusted by adjusting doping or stoichiometry. However, there are few investigations on the LSPRs of bimetal copper-based chalcogenides. Herein, bimetal Cu5FeS4 (CFS) nanoparticles were synthesized by a facile hot injection of a molecular precursor. The tunable plasmon resonance absorption of CFS nanoparticles is achieved by the decrease of the ratio of copper to iron and the treatment of n-dodecylphosphoric acid (DDPA). After surface modification with polyethylene glycol (PEG), the CFS nanoparticles with a plasmon resonance absorption peak at 764 nm can be served as promising photothermal agents, showing good biocompatibility and excellent photothermal performance with the photothermal conversion efficiency up to 50.5%, thus used for photothermal therapy of cancers under the irradiation of an 808 nm laser. Our work provides the insight of bimetal copper-based chalcogenides to achieve the tunable LSPRs, which opens up the possibility of rationally designing plasmonic bimetal copper-based chalcogenides